The Difference Between the Healing and the Nonhealing Diabetic Foot Ulcer: A Review of the Role of the Microcirculation. (September 2017) - Lowry, Danielle; Saeed, Mujahid; Narendran, Parth; Tiwari, Alok
Background: Diabetic foot disease carries a high morbidity and is a leading cause of lower limb amputation. This may in part be due to the effect diabetes mellitus (DM) has on the microcirculation including in the skin. Method: We conducted a review of studies that have examined the relationship between microcirculatory function and wound healing in patients with DM. A search of the Medline, Embase, and Web of Science databases was performed coupled with a review of references for the period 1946 to March 2015. Results: Nineteen studies of diverse methodology and cohort selection were identified. Poor function of the microcirculation was related to poor outcome. Transcutaneous oxygen pressure (TcPO2 ) was the most commonly used method to measure the microcirculation and thresholds for poor outcome proposed ranged from 10 mmHg to <34 mmHg. Two studies reexamined microcirculatory function following revascularization. Both found an increase in TcPO2, however only 1 reached statistical significance. No significant difference in the results of microcirculation tests was found between diabetic and nondiabetic patients. Conclusions: While it is not possible to draw firm conclusions from the evidence currently available there are clear areas that warrant research. Good microcirculation unsurprisingly appears to associate with better wound healing. The influence of DM is not clear, and neither is the degree of improvement required to achieve healing. Studies that examine a clearly defined cohort both with and without DM are urgently required. Accurate quantitative assessment of microcirculation will aid prediction of wound healing identifying those at greatest risk of amputation.